Perancangan Motif Berbasis Wastra Batik Jawa Hokokai Untuk Produk Fesyen Generasi Milenial - Paulina Tjandrawibawa; Marini Yunita Tanzil (JURNAL RUPA, 2022)
Indonesian batik has been known as one of the world's artistic cultural heritages. Based on data from the Ministry of Industry of the Republic of Indonesia in 2020, the batik industry is also one of the sectors that are considered to have great potential in generating national economic growth. According to Katadata Insight Center Research, 85% of e-commerce transactions are dominated by Generation Z consumers (born 1997-2012, aged 9-25 years in 2021) and Millennials (born 1981-1996, aged 25-40 years in 2021). Therefore, by seeing this potential, this study aims to create batik motifs that can attract the attention of the younger generation by applying a loungewear pattern, namely casual clothes that are comfortable to wear but still suitable to be worn outside the home or for online meetings. The traditional batik that will be used in this research is the Javanese Batik Hokokai, because it has a storythat can be a separate story to be conveyed to the younger generation.